Desiccant drying prior to hermetic storage extends viability and reduces bruchid (Callosobruchus chinensis L.) infestation of mung bean (Vigna radiata (L.) R. Wilczek) seeds. (December 2021) - Sultana, Razia; Kunusoth, Keshavulu; Amineni, Lakshmiprasad; Dahal, Peetambar; Bradford, Kent J.
Abstract: Seeds of mung bean ( Vigna radiata (L.) R. Wilczek) are subject to loss of viability due to aging and damage from pulse beetles (or bruchids; Callosobruchus spp.) infestation during storage. We investigated whether seed drying using desiccants and hermetic packaging would prevent or ameliorate these consequences of storage. Sun-dried mung bean seeds at a moisture content of 10% were subjected to further drying for 72 h using five different desiccants: Drying Beads® (a zeolite-based desiccant), silica gel, sodium aluminum silicate, activated alumina, and cow-dung ash (a traditional desiccant). Seeds were subsequently stored in hermetic plastic containers in the presence of these desiccants under ambient conditions along with sun-dried seeds stored in cloth bags or in hermetic containers. In addition, parallel samples of each treatment were inoculated with one pair of bruchid beetles ( C. chinensis L.) and stored under the same conditions. The seed drying treatments did not affect initial seed quality (germination percentage and seedling vigor) significantly. After storage for 9 months at ambient temperatures, seeds dried using Drying Beads, silica gel, sodium aluminum silicate and activated alumina had higher germination percentages, seedling vigor indices and soil emergence, and lower electrical conductivity (leakage upon imbibition) and fungal infestation compared to other conditions. In addition, the mung bean seeds inoculated with bruchids and stored with these effective desiccants had less damage, oviposition, and insect respiratory activity in the hermetic containers and maintained higher seed germination and seedling vigor after six months of storage compared to other treatments and controls. The results demonstrate the superior ability of desiccants to quickly and safely dry seeds prior to and during storage and the benefits of such drying and hermetic storage conditions for preventing seed deterioration and insect damage during storage. Highlights: Mung bean seeds lose viability and are damaged by bruchid beetles during storage. Drying to low moisture contents maintains seed quality and kills bruchid beetles. Effective desiccants (e.g., Drying Beads) and hermetic storage preserve seed quality.